Chronic Voluntary Binge Ethanol Consumption Causes Sex‐Specific Differences in Microglial Signaling Pathways and Withdrawal‐associated Behaviors in Mice. (6th September 2020) - Rath, Meera; Guergues, Jennifer; Pinho, Joao P.C.; Zhang, Ping; Nguyen, Truc G.; MacFadyen, Kaley A.; Peris, Joanna; McLaughlin, Jay P.; Stevens, Stanley M.; Liu, Bin
Abstract : Background: Microglia are the resident immune cells in the brain where they play essential roles in the development and maintenance of physiological functions of this organ. Aberrant activation of microglia is speculated to be involved in the pathogenesis of a variety of neurological disorders, including alcohol use disorders. Repeated binge ethanol (EtOH) consumption can have a profound impact on the function and integrity of the brain resulting in changes in behaviors such as withdrawal and reward. However, the microglial molecular and cellular pathways associated with EtOH binge consumption remain poorly understood. Method: In this study, adult C57BL/6J male and female mice were subjected daily to a gelatin‐based drinking‐in‐the‐dark voluntary EtOH consumption paradigm (3 h/d for 4 months) to characterize EtOH consumption and withdrawal‐associated and anxiety‐like behaviors. Brain microglia were isolated at the end and analyzed for protein expression profile changes using unbiased mass spectrometry‐based proteomic analysis. Results: Both male and female mice consistently consumed binge quantities of EtOH daily, resulting in blood EtOH levels > 80 mg/dl measured at the end of the 3‐hour daily consumption period. Although female mice consumed a significantly greater amount of EtOH than male mice, EtOH withdrawal‐associated anxiety‐like behaviors measured by marble‐burying, light‐dark box, and elevated plus maze tests were predominantly observed in male mice. Proteomic analysis of microglia isolated from the brains of animals at the end of the 4‐month binge EtOH consumption identified 117 and 37 proteins that were significantly up‐ or downregulated in EtOH‐exposed male and female mice, respectively, compared to their pair‐fed controls. Protein expression profile‐based pathway analysis identified several cellular pathways that may underlie the sex‐specific and EtOH withdrawal‐associated behavioral abnormalities. Conclusion: Taken together, our findings revealed sex‐specific changes in EtOH withdrawal‐associated behaviors and signaling pathways in the mouse brain microglia and may help advance our understanding of the molecular, cellular, and behavioral changes related to human binge EtOH consumption. Abstract : Over a 4‐month ethanol binge, adult female mice had a greater daily ethanol intake (A) resulting in a higher blood ethanol level (B) than male mice. Yet, anxiety‐like behaviors, such as that measured as the number of marbles buried during withdrawal, were far more pronounced in the male than the female ethanol‐consuming mice (B). Proteomic analysis revealed changes in expression levels of a far greater number of proteins in brain microglia from male ethanol mice than their female counterparts (C).